A212 ENDOSCOPIST-DIRECTED PROPOFOL AS AN ADJUNCT TO STANDARD SEDATION: A CANADIAN EXPERIENCE. (1st March 2018) - Heron, V; Golden, C; Battat, R; Galiatsatos, P; Stein, B L; Wyse, J; Cohen, A
Abstract: Background: Sedation practices vary widely by region. In Canada, endoscopist-directed administration of a combination of fentanyl and midazolam is standard practice, with only a minority of cases performed with propofol. Aims: To demonstrate the safety of non-anesthetist administered propofol for endoscopic sedation. Methods: This was a single-centre retrospective cohort study of patients having undergone endoscopic procedures with propofol sedation between 2004 and 2012 in an academic hospital in Montreal. Procedures were performed by gastroenterologists trained in Advanced Cardiovascular Life Support. Sedation was administered by IV bolus by a registered nurse, under the direction of the endoscopist. Outcomes of procedures were collected using the hospital's endoscopy database. Results: 4955 patients were included. Cecal intubation rate for colonoscopies (n=2920) was 90.0%. Gastroscopies (n=1625), flexible sigmoidoscopies (n=28), ERCP (n=341) and PEG insertion (n=41) had success rates of 98.4%, 96.4%, 94.4% and 92.7% respectively. The average dose of propofol used for each procedure was 34.6 mg. Fentanyl was used in 68% of procedures at an average dose of 94.4 mcg. Versed was used in 92.9% of cases at an average dose of 3.0 mg. Reversal agents (naloxone or flumazenil) were used in 0.4% of cases (n=21). Patients having received reversal agents were discharged uneventfully within the usual post-procedure recovery time. One patient required transfer to the ER. Most patients having received propofol in addition to standard sedation agents experienced no adverse events (99.6%). There were no deaths. Conclusions: The use of propofol administered by a registered nurse under the direction of the endoscopist as an adjunct to fentanyl and versed is safe and effective. Funding Agencies: None